BODY IMAGE AND PSYCHOLOGICAL DISTRESS AMONG UNIVERSITY STUDENTS - Rashid, Zoha; Arzeen, Naeema; Shah, Mubashir (Journal of Postgraduate Medical Institute, 2021)
Objective: To find out the relationship between body image and psychological distress among university students. Methodology: This cross-sectional study was conducted on 250 participants enrolled from universities of Islamabad with age range of 18 to 25 years. Two scales; Body Image Concern Inventory (BICI) and Kessler’s Psychological Distress Scale (K-10) were used to measure the variables. Data was entered and analyzed by SPSS version 21. Results: The findings indicated that there was significant positive correlation (r=0.63**) between body image concern and psychological distress. Further, male students showed higher concern as compared to female students (t (248) =2.45, p < .01). Regression analysis indicated the value of R2 that was 40 % of the total variability in psychological distress that was explained by body image concern. Conclusion: The study concluded a significant positive correlation between body image concern and psychological distress. In addition, male students were more concerning than the female students.